LARANGAN PERNIKAHAN BEDA AGAMA DALAM PERSPEKTIF SYAD ZARIâ€™AH IMAM AL-SYATIBI - Sunarto, Muhammad Zainuddin (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
Social relations in modern times is now very universal, without limitation of religion, race, and class, then it allows two people of different religions into love, affection, and was about to enter into marriage. On the other hand, freedom of religion in Indonesia is guaranteed in the Constitution and protected in points on human rights. In Islamic law known several methods in the determination of a law one of which is Syad Zariâ€™ah, is defined as preventive measures to avoid the ugliness. Imam al-Syatibi, One philosopher of Islamic law has its own ideas about these methods. In Usul al-Fiqh Study, Syad Zariâ€™ah interpreted as closing the road that leads to destruction. Imam al-Syatibi at defining about Syad Zariâ€™ah â€œdo a job which all contain kindness changed to an uglinessâ€. someone doing a job that basically allowed because it contains a kindness, but the objectives to be achieved end on an ugliness. haram law in this case not because of his own actions, but the law forbidden here because the objectives to be achieved from such actions. this is called the practice of Syad Zariâ€™ah. This method is deemed the application form from the rules of fiqh â€œdarâ€™u al-mafasid muqaddamun â€˜ala jalbi al-masalihâ€. From the other side, haram law here is also based of maqasid syariâ€™ah in keeping religion in order to avoid switching to another religion